Pengaruh Perlakuan Sexing terhadap Konsumsi Pakan, Pertambahan Berat Badan, dan Konversi Pakan Ayam Ras Pedaging di Kandang Semi Closed House - Herry Susanto; Herawati M; Rastosari A (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2019)
The purpose of this study was to test and evaluate feed intake, average daily gain and feed conversion ratio of male and female broilers with a separate maintenance treatment (sexing) in semi-closed house cages. The study was conducted at Joni Farm, Tegineneng Subdistrict, Pesawaran District. The type of research used was experimental research comparing the performance of male and female broilers that were kept separately (sexing) at the age of 12 days to 30 days. Experimental broilers used during research were 94 male and 94 female Lohmann. The variables observed in this study were male and female broiler on feed intake, average daily gain (ADG) and Feed Convertion Ratio (FCR). Based on the results of statistical analysis showed sexing has a significant effect on ADG and FCR. Sexing had no effect on feed intake. The average feed intake of male broiler chicken feed was 128.12 grams, while the consumption of female broiler was 120.00 grams. Average daily gain (ADG) of male broiler was higher than female broiler , ADG male broiler were 75.61 grams, while ADG female broiler were 66.28 grams. FCR of female broilers was 1.77 wich higher than male broilers was 1.57. Keywords: Average Daily Gain, Feed Convertion, Feed Intake, Sexing Chicken Broiler